Cardio‐metabolic risk factors among young infertile women: a systematic review and meta‐analysis - Mulder, CL; Lassi, ZS; Grieger, JA; Ali, A; Jankovic‐Karasoulos, T; Roberts, CT; Andraweera, PH (BJOG : an international journal of obstetrics and gynaecology, 2020)
Background There is currently no concise systematic review or meta‐analysis addressing cardio‐metabolic risk factors in women experiencing infertility. Objectives To determine whether infertile women have higher levels of cardiovascular risk factors compared with fertile women. Search strategy We performed a systematic literature search using PubMed, Embase and CINAHL, Scopus and additional manual and bibliographic searches for relevant articles (end search date 6 November 2019). Selection criteria We selected studies that compared cardio‐metabolic risk factors in fertile and infertile women of reproductive age. Data collection and analysis At least two authors independently screened potentially eligible studies. Main results There was an increased presence of several cardio‐metabolic risk factors in infertile women compared with fertile women. Infertile women had statistically significant higher body mass index (BMI), increased total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C) and triglycerides (TG) compared with fertile women. Fasting glucose, fasting insulin, homeostatic model assessment of insulin resistance (HOMA‐IR) and mean arterial pressure were not found to be different between fertile and infertile women. A subgroup analysis revealed that TC, fasting glucose and fasting insulin were increased, and high‐density lipoprotein was decreased only in women with polycystic ovarian syndrome compared with fertile women, whereas BMI, TG and LDL‐C were statistically significantly increased in women with any indication of infertility compared with fertile women. Conclusions Infertile women have a higher level of cardio‐metabolic risk factors compared with fertile women. This finding has clinical implications for infertile women in general, and those attempting to conceive through medically assisted reproduction. Tweetable Infertile women appear to have a higher level of cardio‐metabolic risk factors compared with fertile women. Tweetable Infertile women appear to have a higher level of cardio‐metabolic risk factors compared with fertile women.